A study of fetomaternal outcome in singleton pregnancies with cord around neck - Gahlot, Ankita; Vyas, Jyotsna; Himani, Sunita; ., Ekta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Entanglement of umbilical cord around the foetal neck is a common finding at ultrasonography. A nuchal cord occurs when the umbilical cord becomes wrapped around the foetal neck by 360°. Nuchal cord is very common, with the prevalence rates of 6-37%. Up to half of nuchal cords resolve before delivery. Methods: This study was conducted on 100 women irrespective of parity with healthy singleton term pregnancies with cephalic presentation in the department of obstetrics and gynaecology, SMS Medical College Jaipur. They were included in study after applying inclusion criteria and a written informed consent was taken. Strict fetomaternal monitoring was done during labour and data was interpreted in terms of percentage. Results: Out of 100 cases 71% delivered vaginally, 29% underwent caesarean section. None of the caesarean was done for cord around neck as the only indication. The indications for caesarean section were previous caesarean (34.4%), preeclampsia (13.7%), severe oligohydramnios (31%) and non-reassuring foetal heart rate (20%). Among the women who delivered normally, 53% had single loop, 29.5% had two loops, 14% had three loops and 2% had more than 3 loops. Among women who underwent caesarean section, 65% had single loop, 31% had two loops and 14% had more than two loops. Regarding neonatal outcome 9% neonates were admitted in NICU for reasons like meconium aspiration (33.3%), preterm (44%) and preeclampsia (22%). Conclusions: Cord around neck per se is not an indication for caesarean section and these cases can be delivered vaginally if careful intrapartum monitoring is done.